2013
DOI: 10.1182/blood-2012-10-460832
|View full text |Cite
|
Sign up to set email alerts
|

P110α-mediated constitutive PI3K signaling limits the efficacy of p110δ-selective inhibition in mantle cell lymphoma, particularly with multiple relapse

Abstract: Key Points• The increased expression of PI3K p110a in mantle cell lymphoma, particularly at relapse, suggests a role for p110a in disease progression.• A high PIK3CA/PIK3CD ratio identifies patients unlikely to respond to p110d inhibitors and supports use of dual p110a/p110d inhibitors in MCL.Phosphoinositide-3 kinase (PI3K) pathway activation contributes to mantle cell lymphoma (MCL) pathogenesis, but early-phase studies of the PI3K p110d inhibitor GS-1101 have reported inferior responses in MCL compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(104 citation statements)
references
References 34 publications
5
95
3
1
Order By: Relevance
“…In this sense, it has been reported that expression of p110 isoform can maintain constitutive PI3K signaling despite p110 inhibition. 36 The inhibition of PI3K by NVP-BKM120 results in dephosphorylation of Akt and subsequent regulation of a number of proteins including FoxO3a. The tumor suppressor genes of the FoxO subfamily of Forkhead transcription factors that includes FoxO3a (or FKHRL1), FoxO1a (or FKHR), and FoxO4a (or AFX) are critical effectors downstream of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, it has been reported that expression of p110 isoform can maintain constitutive PI3K signaling despite p110 inhibition. 36 The inhibition of PI3K by NVP-BKM120 results in dephosphorylation of Akt and subsequent regulation of a number of proteins including FoxO3a. The tumor suppressor genes of the FoxO subfamily of Forkhead transcription factors that includes FoxO3a (or FKHRL1), FoxO1a (or FKHR), and FoxO4a (or AFX) are critical effectors downstream of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…Objective response rates were seen in about 50% of the patients with relapsed or refractory B-cell malignancies (41,42). Although GS-1101 shows great potential as a candidate therapy for CLL and NHL, some recent studies with experimental models have suggested that pan-class I PI3K inhibition could offer broader activity in a variety of hematologic malignancies (43)(44)(45). Such observations should be treated with caution: although GS-1101 demonstrated moderate activity during preclinical development, it has shown impressive activity in the clinical setting, which has been attributed to its action on the tumor microenvironment, as opposed to its activity within leukemia and lymphoma cells themselves (46).…”
Section: P110d Inhibitors Versus Pan-pi3k and Dual Pi3k/ Mtor Inhibitmentioning
confidence: 99%
“…Analysis of MCL cell lines and primary samples suggest that PIK3CA amplification may be a mechanism of resistance to p110d inhibition. 35 Hodgkin's lymphoma PI3K is constitutively activated in Hodgkin's and ReedSternberg (HRS) cells and is associated with prolonged cell survival. 62 In Hodgkin's lymphoma (HL) cell lines, PI3Kd was detected at higher levels than other class I PI3K isoforms.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%
“…While PI3Kd was the most consistently expressed, PI3Kα expression was significantly greater in patients with MCL who had relapsed multiple times and PIK3CA amplification was associated with resistance to p110d inhibition. 35 Several ongoing trials are evaluating GDC-0941, including a phase I dose-escalation study in patients with NHL or solid tumors (clinicaltrials.gov identifier:00876122). Preliminary results in patients with solid tumors have been reported.…”
Section: Pi3k Inhibitors In Hematologic Malignanciesmentioning
confidence: 99%